CNC-loaded hydrogel particles generated from single- and double-emulsion drops. Issue 1 (March 2015) - Ye, Congwang; Kennedy, Lauren; Shirk, Kathryn; Córdova-Figueroa, Ubaldo M.; Youngblood, Jeffrey; Martinez, Carlos J.
Abstract : Cellulose nanocrystal (CNC) suspensions were processed for the first time in microcapillary microfluidic devices with the goal of fabricating CNC-loaded monodisperse hydrogel particles from single- and double-emulsion drops. CNC suspensions ranging from 2 to 12 wt% showed an increase in viscosity and shear thinning due to strong nanofiber interactions in solution. Despite their high viscosities, it was possible to generate monodisperse single-emulsion drops in polydimethylsiloxane oil with CNC concentrations up to 12 wt% and diameters ranging from 15 to 150 µm. CNC–poly(ethylene glycol) diacrylate (PEGDA) hydrogel particles with concentrations up to 10 wt% and sizes ranging from 50 to 80 µm were also generated from single-emulsion drops and survived cleaning, drying and re-hydration. CNC–PEGDA hydrogel particles with concentrations up to 61 wt% were obtained from double-emulsion drops. Overall, this study demonstrates a robust path for the fabrication of CNC-loaded hydrogel particles using microcapillary devices.